AFFIXATION IN LANGUAGE LEARNING - Shaymardanova Farangiz,; Tursunova Munira,; Furqatova Bonu, (TADQIQOTLAR, 2026)
Annotation This article discusses the concept of affixation and its importance in language learning.  Affixation  is  a  word-formation  process  that  involves  adding  prefixes  and suffixes to base words to create new meanings. The study highlights how affixation helps  learners  expand  vocabulary,  improve  grammar  skills,  and  understand  word structure.  It  also  explains  how  affixation  supports  effective  communication  and language development.